2018
DOI: 10.1186/s40001-017-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COX-2 inhibition on tendon-to-bone healing and PGE2 concentration after anterior cruciate ligament reconstruction

Abstract: BackgroundNon-steroidal anti-inflammatory drugs are commonly used to reduce pain and inflammation in orthopaedic patients. Selective cyclooxygenase-2 (COX-2) inhibitors have been developed to minimize drug-specific side effects. However, they are suspected to impair both bone and tendon healing. The objective of this study is to evaluate the effect of COX-2 inhibitor administration on tendon-to-bone healing and prostaglandin E (PGE2) concentration.MethodsThirty-two New Zealand white rabbits underwent reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 60 publications
0
46
0
Order By: Relevance
“…Therefore, additional hyaluronidase sessions are usually needed for patients receiving fillers with higher HA concentration [ 10 ]. However, different studies have demonstrated contradictory results attributed to disparities in hyaluronidase source (bovine, ovine, recombinant human), doses used, as well as diverse experimental formats [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, additional hyaluronidase sessions are usually needed for patients receiving fillers with higher HA concentration [ 10 ]. However, different studies have demonstrated contradictory results attributed to disparities in hyaluronidase source (bovine, ovine, recombinant human), doses used, as well as diverse experimental formats [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…HA filler degradability by hyaluronidase can be considered as a “safety-feature” and gives a filler a potential edge over its competitors [ 9 ]. Technical errors, such as overfilling/overcorrection or filler placement at the wrong soft tissue plane or misplacement, may be reversed by hyaluronidase administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NSAIDs have so many advantages, these drugs have been reported to potentially impair musculoskeletal healing in several previous basic experimental studies [ 12 , 13 , 28 , 29 ]. These experimental studies found that NSAIDs could have a negative effect in decreasing inflammatory cell signaling during inflammatory and proliferative phase of tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, selective COX-2 inhibitors, including celecoxib, have become more popular because they can provide similar effect in pain control and reduce incidence of side effects of traditional NSAIDs and opioid [ 11 ]. However, recent basic science studies have reported selective COX-2 inhibitors could impair tendon-to-bone healing, weakening mechanical stability of joints [ 12 , 13 ]. Whether selective COX-2 inhibitors postpone healing of ACL resulting in reduced functional outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%